Global marketing : foreign entry, local marketing, & global management - Johansson, Johny K. (McGraw-Hill Irwin, 2009)
"Johansson's Global Marketing, 5/e utilizes a three-pronged framework to organize the discussion of how to conduct global business: Foreign Entry, Local Marketing, and Global Management. Johansson seeks to develop the varied skills a marketing manager needs to be successful in each of these tasks. In foreign entry, in global management, and to a large extent even as a local marketer in a foreign country, the global marketer needs skills that the home makes experience-or the standard marketing text-have rarely taught. The recognition of the three roles helps dispel the notion that "there is no such thing as international global marketing, only marketing. Much of the excellent research and tried-and-true teaching material that global marketers in business and academe have contributed over the years is reflected in the chapters and in several cases that can be found at the end of each major section. The authors have focused on material that is timely and up-to-date, and relevant to the global context."--Publisher's website.